Transferred, Preserved, and Destroyed: The Dominion Lands Branch’s Manitoba Files - Eyford, Ryan (Archivaria, 2023)
During the 1950s, the Province of Manitoba microfilmed and then destroyed thousands of files created by the federal Department of the Interior’s Dominion Lands Branch (DLB). These records, dating from about 1870 to 1930, were transferred from the federal government to the province in the immediate post-war period. They were drawn from a group of more than 5.6 million files occupying 11,640 square feet of office space in downtown Ottawa. During the Second World War, the civil servants responsible for the DLB files were pressured by their superiors to destroy the files in order to free up space and filing cabinets. DLB officials, although not trained archivists, took their responsibility as custodians of the records seriously and sought to prevent the wholesale and indiscriminate destruction of the files. They were supported by archivists who considered the DLB files to be valuable historical documents on the colonization of Western Canada. Eventually, the conflict between preservation and destruction was resolved by dispersing the records; some were transferred to the western provinces and territories, while the remaining files were deposited in the Public Archives of Canada. The first files to be transferred were those related to lands in Manitoba. This article clarifies the provenance of the DLB’s Manitoba files and argues for their enduring value as records of the history of settler colonialism in the province while also revealing the role of non-archivist civil servants as custodians of government records in the mid- 20th century.